Louis VI of France in the battle (engraving) - Auteur inconnu (Wikimedia Commons, 1860)
Notice iconographique issue de Wikimedia Commons. Titre: Louis VI of France in the battle (engraving). Louis VI of France in the battle (engraving)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons